Effect of Post-Partum on The Oestrus Synchronisation with Progesterone and Oestradiol of Bali Cattle - Adji Santoso Dradjat (Faculty of Animal Science, Universitas Gadjah Mada, 2001)
Artikel dalam bentuk PDF